Dimorphic Fungi : Their importance as Models for Differentiation and Fungal Pathogenesis. - Ruiz-Herrera, José (Bentham Science Publishers, 2012)
This e-book includes several chapters on the most important and studied fungal models, written by specialists, discussing the biology of each species or genera, the general aspects controlling their dimorphic transition, the molecular aspects involved, the use of them as models for understanding the bases of biochemical and cell differentiation, and the importance of dimorphism in pathogenesis.